Álvaro Manuel Guimarães e Sousa, o Pioneiro da Cirurgia Plástica em Portugal - Patrícia Ana Teixeira da Costa (2020)
Background: Álvaro Guimarães e Sousa (b.1923) was the pioneer of Plastic Surgery (PS) in Portugal. He fought for it to be considered a specialty distinct from General Surgery. The purpose of this dissertation is to clarify how PS emerged in our country and, at the same time, to praise the Surgeon who was its driving force. Methods and Materials: The bibliographical research was based on documents in his possession, on the book he published, on the first three Books of Minutes of the Portuguese Society of Reconstructive and Aesthetic Plastic Surgery (SPCPRE) and on interviews with him. The photographic record and inventory of the books that were part of its Private Library of PS, as well as of its surgical instruments, was also carried out. Results: After specializing in PS in Oxford, in 1964 he managed to create the specialty in Portugal. He worked as director of the first Reconstructive and Plastic Surgery (RPS) Unit that he organized at Hospital Geral de Santo António (HGSA) and, later, at Hospital Rodrigues Semide (HRS), both in Oporto. He was at the forefront of the planning and execution of the Hospital da Prelada (HP) project, Oporto, in particular of the Burns Unit. Discussion: His journey was made of overcoming challenges. Those were the creation of RPS as a medical specialty, the creation of the first unit, the obtainment of the HP project and of the first Burns Unit in Portugal. Conclusion: Álvaro Guimarães e Sousa was the founder of the first RPS Unit and Burns Unit in our country. This latter initiative has never been recognized by its peers. Keywords: Álvaro Guimarães e Sousa, Beginning of Plastic Surgery in Portugal, History of Medicine, History of Plastic Surgery.